Prevalence of Sexual Dysfunction in Patient with Subclinical Hypothyroidism and Subclinical Hyperthyroidism - Sana, Zakirullah Khan, Bakht Babar, Jamal Ahmad Khan, Azmat Ali Khan (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Thyroid disease as well as sexual dysfunction is both prevalent disorders that can significantly impact one’s quality of life. Objectives: To determine the prevalence of sexual dysfunction in patient with hypothyroidism and hyperthyroidism. Study design: Cross sectional study Settings: Department of Diabetes, Endocrinology and Metabolic Diseases, MTI Hayatabad Medical Complex, Peshawar from December 2022 to May 2023. Materials & Methods: The study included adult individuals (aged 18 and above) with a confirmed diagnosis of hypothyroidism. Individuals with pre-existing sexual dysfunction unrelated to hypothyroidism, those with comorbidities affecting sexual function (diabetes, cardiovascular diseases), and pregnant or lactating women were excluded. Additionally, individuals unable to complete the required questionnaires or participate in the study procedures were not considered for inclusion. Participants provided demographic details, including age, gender, and relevant medical history. Thyroid function was assessed through serum levels of thyroid-stimulating hormone (TSH), triiodothyronine (T3), and thyroxine (T4). Statistical analysis was performed using SPSS version 22. Results: The mean age of the participants was 42.5 years, with a standard deviation of 8.2 years. In terms of gender, there were 82 male participants, constituting 65.6% of the total, while 38 participants were female, representing 31.66%. For subclinical hypothyroidism, the levels of FSH were 8.90 ± 4.50 mU/mL, LH was 7.20 ± 3.90 mU/mL, Free Testosterone was 5.60 ± 2.40 pg/mL, and Prolactin was 350.60 ± 75.80 ng/mL. For subclinical hypothyroidism, 78.33% of male patients and 41.66% of female patients were affected. In the case of subclinical hyperthyroidism, 61.66% of male patients and 36.66% of female patients had this condition. Practical Implication: The study’s findings offer actionable insights for policymakers, facilitating informed decisions in healthcare resource allocation. Implementation of these recommendations can enhance patient outcomes and optimize resource utilization effectively. Conclusion: In conclusion, our study underscores the significant association between subclinical hypothyroidism and sexual dysfunction, aligning with and extending findings from existing literature Keywords: Subclinical Hypothyroidism, Subclinical Hyperthyroidism, Sexual Dysfunction, Thyroid Disorders